2022
DOI: 10.1186/s12888-022-04283-6
|View full text |Cite
|
Sign up to set email alerts
|

High smoking and low cessation rates among patients in treatment for opioid and other substance use disorders

Abstract: Background: Smoking is a well-documented cause of health problems among individuals with substance use disorders. For patients in opioid maintenance treatment (OMT), the risk for somatic health problems, including preventable diseases associated with tobacco smoking, increases with age. Our aim was to describe smoking among patients entering substance use disorder (SUD) treatment, investigate changes in smoking from the start of treatment to 1-year follow-up, and explore factors related to smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…High somatic comorbidity is common among patients in OMT treatment, and patients in OMT are at increased risk of developing comorbidities, such as respiratory and cardiovascular diseases (CVDs) [ 6 9 ]. High levels of smoking and smoking-related harms are particularly prominent in OMT populations [ 8 , 10 , 11 ]. Thus, somatic disease is a major concern for these patients, and non-drug-related premature causes of death are more prevalent than in the general population [ 5 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High somatic comorbidity is common among patients in OMT treatment, and patients in OMT are at increased risk of developing comorbidities, such as respiratory and cardiovascular diseases (CVDs) [ 6 9 ]. High levels of smoking and smoking-related harms are particularly prominent in OMT populations [ 8 , 10 , 11 ]. Thus, somatic disease is a major concern for these patients, and non-drug-related premature causes of death are more prevalent than in the general population [ 5 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in OMT report lower health-related quality of life [ 20 ], and somatic symptoms, such as pain, have been associated with medical and psychological comorbidities [ 21 , 22 ]. A previous publication on a subsample of older patients in OMT from the Norwegian Cohort of Patients in OMT and Other Drug Treatment (NorComt) study reported an association between mental distress and chronic conditions and levels of somatic symptoms [ 10 ]. Individuals with OUD in OMT are more likely to reach a higher age than individuals with OUD who are not in OMT [ 3 , 5 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer remains a significant global health challenge, ranking among the leading causes of death world-wide. Past studies have reported increased cancer risk and cancer mortality among people with opioid use-related disorders which can possibly be explained by a high burden of several life-style factors, including smoking, alcohol use and injection drug behaviour, which elevates the risk of hepatitis-related cancers [1][2][3][4][5][6][7][8][9][10]. However, this population is known to have higher rates of suicide, poisoning and other unnatural deaths [11][12][13], which may lead to lower cancer-related mortality due to a higher risk of premature mortality from competing risks compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…CI = confidence interval; Expected, = expected number of cancer deaths based on person-years at risk compared to age-and sex-matched general population; ICD-10 = International Classification of Disease; Observations: observed number of cancer deaths. as hepatitis C) and alcohol use, significantly increasing the risks of lung, liver and pancreas cancer[1][2][3][4][5][6][7][8]10]. Moreover, emerging research suggests a possible link between opioids and cancer development and progression, potentially further elevating the risk among people using opioids on a regular basis[27].…”
mentioning
confidence: 99%
“…Pharmacologic and behavioral interventions effectively increase smoking cessation in the general adult population ( 14 ). However, smoking cessation seems harder to achieve among people with opioid use disorders ( 15 , 16 ) including patients receiving OAT ( 17 , 18 ). Pharmacotherapies, such as nicotine replacement or varenicline have modest effect rates for smoking cessation among methadone maintained, and other patients with opioid use disorder ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%